The Mediating Role of Knowledge Management on the Relationship between Human Resource Management Practices and Organizational Performance: Case Study of Faculty of Economic and Commercial Sciences and Management Sciences in Tahri Muhammed University Becher -Algeria - الهزام , محمد; عيساوي, فاطمة (Finance and Business Economies Review, 2021)
The study aimed to identify the direct impact of HRM practices on organizational performance, and the indirect impact through knowledge management at Tahri M. Bechar University, Algeria. In order to achieve the goal of the study, a questionnaire was designed based on relevant studies to collect data from the study sample,which is represented by 48 teachers. The study found a number of results, the most important are:The existence of a statistically significant effect of HRM practices on organizational performance, and the existence of a statistically significant effect of knowledge management as a mediator in the relationship between HRM practices and organizational performance at Tahri. M Bechar University, Algeria. The most important recommendations are: The need to use HRM practices effectively in order to be able to develop its performance, and the necessity of alignment between the strategy of HRM with the strategy of applying knowledge management to ensure a high level of organizational performance